2018
DOI: 10.1002/tcr.201800015
|View full text |Cite
|
Sign up to set email alerts
|

A Recent Perspective on Noncovalently Formed Polymeric Hydrogels

Abstract: Chemically crosslinked covalent hydrogels form a permanent and often strong network, and have been extensively used so far in drug delivery and tissue engineering. However, it is more difficult to induce dynamic and highly tunable changes in these hydrogels. Noncovalently formed hydrogels show promise as inherently reversible systems with an ability to change in response to dynamic environments, and have garnered strong interest recently. In this Personal Account, we elucidate a few key attractive properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 137 publications
1
30
0
Order By: Relevance
“…2) [45]. Hydrogels have been used as promising materials for a variety of ophthalmic applications [46][47][48][49][50][51][52][53]. However, developing sustained drug delivery systems for biologics such as anti-VEGF molecules is a challenging task.…”
Section: Novel Sustained Drug Delivery Systems For Anti-vegf Agentsmentioning
confidence: 99%
“…2) [45]. Hydrogels have been used as promising materials for a variety of ophthalmic applications [46][47][48][49][50][51][52][53]. However, developing sustained drug delivery systems for biologics such as anti-VEGF molecules is a challenging task.…”
Section: Novel Sustained Drug Delivery Systems For Anti-vegf Agentsmentioning
confidence: 99%
“…Self-healing and shear-thinning properties of supramolecular hydrogels have been demonstrated in different types of polymeric entities (Abdul Karim and Loh, 2015;Kai et al, 2015;Xue et al, 2018). Studies have found that the complexation with non-covalent interaction made the hydrogels reversible under shear cycles (Xue et al, 2018). Studies have also reported the sustained release properties for these materials (Ye et al, 2015;Abdul Karim et al, 2016).…”
Section: Supramolecular Guest-host Interactionsmentioning
confidence: 99%
“…Hydrogels, in particular, can potentially be a useful three-dimensional scaffold for tissue engineering 2 due to their flexibility and water retention ability, similar to biological tissues. [3][4][5][6][7][8][9][10][11] The prefix ''hydro'' indicates hydrophilicity although most gel structures do not dissolve in water. 12 However, the hydrophilicity renders such gel structures capable of holding large amounts of water in their three dimensional networks.…”
Section: Introductionmentioning
confidence: 99%